Malaysian luscious vending machine / Nor Sara Nadia Muhamad Yunus … [et al.] - Muhamad Yunus, Nor Sara Nadia; Mohd Rashid, Norhidayah; Mohd Ariffln, Norafifa; Badrolhisam, Nur Idayu (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
Malaysian Luscious Vending Machine is another way to introduce Malaysia cuisine by enhancing the existing Malaysia Kitchen Program. This vending machine will be a very good indicator in estimating demand of Malaysian cuisine in overseas prior the development of Malaysia Kitchen chains of restaurant. It is aligned with 'Malaysia Truly Asia Campaign" in bringing Malaysia’s name worldwide. A part from international objective, Malaysian Luscious Vending Machine is very useful in educating and encouraging local people to consume Malaysian cuisine through vending machine with 24-hour accessibility and it is expected to fulfil local demand due to Malaysian hectic lifestyle. Furthermore, it also reduce the number of value chain members while maintaining quality of Malaysian Halal cuisine locally and internationally. This idea aims to reduce the SME's operating cost, boost the entry point project (EPP) of Economic Transformation Program (ETP) specifically under Tourism and Wholesale & Retail sectors overally.